NATIONAL BRAND AS A TOOL FOR INCREASING THE GLOBAL COMPETITIVENESS OF THE COUNTRY IN THE INTERNATIONAL ENVIRONMENT - NAZARCHUK, Tatiana; TYURINA, Nila; KOVALCHUK, Vitaly (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the national brand as a tool for increasing the country's global competitiveness. The essential characteristics were studied and the category "national brand" was clarified. Its role and significance for the development of macroeconomic stability of the state are substantiated. On the global market, the national brand is one of the most important assets of any state, which helps to attract investments, tourist flows, personnel potential, improve the quality of labor resources, promote the increase in trade export-import operations, and strengthen the innovative component of the country's development.Methodological approaches to rating assessment of national brands are considered. The dynamics of changes in the ranking of the top 10 national brands according to the Global Soft Power Index, as well as the position of Ukraine before and after full-scale military aggression, were studied. In order to determine the influence of the national brand on the level of global competitiveness of the country, the results of the rating of the Institute of Management Development (IMD) were analyzed according to four blocks of indicators: the state of the economy; government efficiency; business efficiency; the state of the infrastructure. Indicators that determine Ukraine's low positions in international competitiveness ratings have been identified, namely: high level of corruption, low credit rating of the country, underdevelopment of the stock market, macroeconomic instability, high level of inflation, low level of health care on the quality of life of the population in general. It is substantiated that the creation of a strong national brand is a guarantee of sustainable economic development of Ukraine, which will also allow positioning the country as attractive for business, tourism and life. An increase in the rating of the country's national brand will contribute to an increase in the inflow of direct investment, and a strong national brand significantly affects the perception of national corporate brands.
Keywords: brand; national brand; branding; evaluation of national brands; competitiveness; rating of global competitiveness; management